High-toughness anti-cracking nickel-based medium-entropy alloy and preparation method and application thereof
By designing the layered structure and precipitation phase structure of high-strength toughness and crack-resistant nickel-based medium-entropy alloy, combined with multi-stage annealing and aging treatment, the shortcomings of medium/high-entropy alloys in strong plasticity matching and fracture toughness are solved, and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202510039414.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
AI Technical Summary
Existing medium/high entropy alloys are difficult to meet the needs of industrial applications at the same time in terms of mechanical properties such as strong plastic matching and fracture toughness.
Through the rational design of alloy composition and precise control preparation process, a layered structure with alternating distribution of residual deformation structure of nano-scale grains and recrystallized structure of micro-scale grains is used, combined with multi-stage annealing and aging treatment, a high-strength, tough, crack-resistant nickel-based medium-entropy alloy with large size and ten-nanometer-scale L12 precipitation phase is formed.
The excellent performance of yield strength of 1259~1298MPa, tensile strength of 1608~1725MPa, elongation of break of 22.1~23.9%, and fracture toughness of 70~100MPa·m1/2 at room temperature, meeting the needs of engineering structural materials.
Smart Images

Figure CN119800160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength, toughness and crack-resistant nickel-based medium-entropy alloy and a preparation method and application thereof, belonging to the technical field of high-performance medium-entropy alloys. Background Art
[0002] In the field of modern materials science, the exploration of high-performance alloy materials has always been the focus. With the rapid development of aerospace, automobile manufacturing, energy and other fields, the requirements for comprehensive properties such as material strength, toughness and fracture toughness have become increasingly stringent, and traditional alloys have been difficult to meet. Medium / high entropy alloys have attracted much attention as emerging material systems. They are composed of three or more main elements with nearly equal molar fractions, and have special inherent properties such as high entropy effect, lattice distortion effect, and hysteresis diffusion effect. These properties can enhance the stability of the solid solution phase, hinder dislocation movement, and give the alloy excellent mechanical properties, heat resistance, wear resistance and creep resistance. They have great application potential in industrial production and have attracted the attention of many material researchers.
[0003] In recent years, although the strength of medium / high entropy alloys has been improved and a certain degree of plasticity has been retained by constructing heterogeneous grain structures through multi-step thermomechanical treatment, the strength and fracture toughness still cannot meet industrial needs. Based on the precipitation strengthening theory, the construction of nano-precipitated phases in the alloy through alloy composition design and specific heat treatment has become an effective strengthening method. Ni 3 Al type L1 2 The precipitated phase is commonly used but has poor ductility. When the alloy is deformed, stress concentration easily leads to premature fracture. The heterogeneous medium-entropy alloy with excellent mechanical properties obtained by combining mechanical treatment and heat treatment meets the country's urgent demand for high-performance metal materials and can also provide reference for improving the performance of other metal materials. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention aims to provide a medium-entropy alloy with excellent strength-plasticity combination and high brittle fracture toughness. By rationally designing the alloy composition and precisely controlling the preparation process, the problem that traditional single-phase face-centered cubic (FCC) structured medium-entropy alloys are difficult to simultaneously meet the requirements of engineering applications in terms of mechanical properties such as strength-plasticity matching and fracture toughness is solved.
[0005] At the same time, the present invention provides a method for preparing a high-strength, tough, and crack-resistant nickel-based medium-entropy alloy. The process parameters of each step in the preparation method are clear and easy to control, such as the melting atmosphere, cold rolling deformation, annealing and aging temperature and time, etc. It has strong operability and is convenient for large-scale industrial production. It can stably prepare medium-entropy alloy materials with excellent performance.
[0006] At the same time, the present invention provides a high-strength, toughness, and crack-resistant nickel-based medium-entropy alloy for use in the fields of aerospace, automobile manufacturing, and energy.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] A high-strength, tough and crack-resistant nickel-based medium-entropy alloy comprises, in atomic percentage, 48-50% Ni, 21-23% Co, 14-16% Cr, 4-6% Al, 4-6% Ti, 0.5-2% Mo, 0.1-0.5% W, 0.1-0.7% Fe, 0.01-0.1% Zr, and the remainder is unavoidable impurities.
[0009] A high-strength, tough, crack-resistant nickel-based medium-entropy alloy having a layered structure with alternating distribution of residual deformation structure of nano-scale grains and recrystallization structure of micron-scale grains; the volume fraction of the residual deformation structure is 12-15%, and the volume fraction of the recrystallization structure is 85-88%; large-size L1 is precipitated in some recrystallized structures 2 Precipitation phase; Spherical ten-nanometer L1 is evenly distributed in the recrystallized structure 2 Precipitation phase; large size L1 2 The size of the precipitated phase is 377-807nm, and the volume fraction is 29-31%; the spherical ten-nanometer L1 2 The size of the precipitated phase is 8.79-9.07 nm, and the volume fraction is 13-15%. The residual deformed structure is embedded with hundreds of nanometer-scale L1 2 The size of the precipitated phase is 86 to 152 nm, and the volume fraction is 4 to 6%.
[0010] Preferably, the medium entropy alloy has two layered structures with alternating grain distribution, namely, a residual deformation structure with smaller grain size, whose volume fraction is 12-15%, and the grain size is 67-130nm; and a recrystallized structure with larger grain size, whose volume fraction is 85-88%, and the grain size is 0.64-1.84μm.
[0011] Preferably, in the dual-phase medium-entropy alloy, there is a precipitated phase in the recrystallization region of the medium-entropy alloy, including L1 precipitated only in part of the grains. 2 Precipitated phase and uniformly distributed spherical ten-nanometer L1 2 The sizes of the precipitated phases are 377-807 nm and 8.79-9.07 nm, respectively, and the volume fractions are 29-31% and 13-15%, respectively.
[0012] Preferably, in the dual-phase medium-entropy alloy, the residual deformation region of the medium-entropy alloy has uniformly distributed spherical L1 2 The precipitated phase has a size of 86 to 152 nm and a volume fraction of 4 to 6%.
[0013] Preferably, the medium entropy alloy has a yield strength of 1259-1298 MPa, a tensile strength of 1608-1725 MPa, an elongation at break of 22.1-23.9%, and a fracture toughness of 70-100 MPa·m at room temperature. 1 / 2 .
[0014] A method for preparing a high-strength, tough, crack-resistant nickel-based medium-entropy alloy comprises the following steps:
[0015] (1) The raw materials of the components are fully melted in an induction melting furnace under an argon atmosphere to obtain an ingot, the melting temperature is 1350-1450° C., the melting time is 15-20 minutes, and the melting number is at least 5 times.
[0016] (2) The ingot in step (1) is subjected to hot forging, homogenization treatment, hot rolling, solution treatment, cold rolling, multi-stage annealing, pre-aging and aging treatment in sequence to obtain a high-strength, tough and crack-resistant nickel-based medium-entropy alloy (named CRAA).
[0017] Preferably, the initial hot forging temperature in step (2) is 1050-1150°C, the final forging temperature is 900-950°C, the hot forging time is 10-15 minutes, and the deformation is controlled at 50-60%. The hot forging can transform the ingot obtained after casting into a primary alloy billet with a rectangular cross section, few as-cast cracks, and a dense structure, which is beneficial to improving the thermoplasticity of the alloy.
[0018] Preferably, the homogenization treatment in step (2) is carried out by keeping the temperature at 1200-1290°C for at least three hours, followed by air cooling. The homogenization treatment in the present invention eliminates dendrites and segregation generated during casting and hot forging, making the alloy structure more uniform and improving its mechanical strength.
[0019] Preferably, in step (2), the hot rolling temperature is 950-1000°C, the total deformation is controlled at 40-50%, the hot rolled surface is the same as the hot forged surface, and finally a hot rolled plate with a thickness of about 15 mm is obtained, and a block alloy sample with a size of 5 mm×10 mm×40 mm is cut from the core of the plate. In the present invention, hot rolling preliminarily refines the grains and provides a higher strength basis for the alloy.
[0020] Preferably, the solution temperature of step (2) is 1090-1120°C, the solution time is 4-6h, and the cooling condition is air cooling to obtain a coarse-grained nickel-based medium-entropy alloy. Solution treatment can make the element distribution uniform, eliminate the internal stress during hot rolling, and improve the strength and stability of the alloy.
[0021] Preferably, the multi-pass cold rolling process parameters of the cold rolling treatment in step (2) need to ensure that the sample thickness is reduced by about 80%, specifically, a homogeneous block sample with an initial thickness of 5 mm is rolled and deformed at room temperature, the average pressure before 2 mm is about 0.2 mm, and the average pressure is changed by about 0.1 mm when rolling about 1 mm, and the final thickness of the deformed rolled plate is 20% of the initial thickness, that is, 1 mm. In the present invention, the cold rolling treatment with a large deformation amount refines the grains to the nanometer level, and introduces a large number of dislocations inside the grains to achieve dislocation strengthening.
[0022] Preferably, the multi-stage annealing temperature of step (2) is 900-1000°C, and the annealing time is 2-24h. Each annealing treatment is based on the previous annealing treatment, and the temperature is increased by 30-50°C and the insulation time is the same; each annealing treatment is air-cooled to room temperature after being taken out of the furnace; two annealing treatments are used. Annealing at the temperature and time causes part of the grain structure to recrystallize, and promotes the formation of precipitation phases in the recrystallized structure and the residual deformation structure, while eliminating the microscopic strain caused by cold rolling. In the present invention, the incomplete annealing treatment enables the alloy to achieve back stress strengthening and precipitation phase strengthening.
[0023] Preferably, the pre-aging treatment temperature of step (2) is 600-650°C, the treatment time is 0.5-1h, and the cooling method is air cooling. The pre-aging treatment in the present invention is conducive to the precipitation of small precipitates, avoiding excessive growth of grain size, and also avoiding excessive coarsening of precipitates produced during annealing, which has a bad effect on performance.
[0024] Preferably, the aging treatment temperature of step (2) is 700-800°C, the aging treatment time is 1-8h, and the cooling method is air cooling. The aging treatment at the temperature and time eliminates some defects in the alloy (such as annealing twins, etc.), ensures that the alloy has good plasticity, and introduces a high number density of tens of nanometers of precipitation phases in the recrystallized grains, strengthens the precipitation phase strengthening effect, and increases the heterogeneity of the alloy, strengthens the back stress strengthening, and further improves the strength of the alloy.
[0025] When the high-strength, toughness, and crack-resistant nickel-based medium-entropy alloy provided by the present invention is subjected to stress loads at room temperature, dislocation slip, mechanical twinning, and stacking faults will occur. Under the combined effect of these defects and multi-sized nano-precipitated phases, the strength of the medium-entropy alloy is significantly enhanced, and better toughness is provided for alloy deformation.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The medium-entropy alloy of the present invention induces L1 through a unique dual heterogeneous interface 2The composition and structural design of precipitation strengthening provide a new idea for the preparation of high-strength and high-plasticity alloys. The yield strength at room temperature is 1259-1298MPa, the tensile strength is 1608-1725MPa, the elongation at break is 22.1-23.9%, and the fracture toughness is 70-100MPa·m 1 / 2 , and has significant advantages in the field of engineering structural materials.
[0028] 2. The microstructure of the entropy alloy in the present invention is layered grains (soft layer recrystallized grains, hard layer nanocrystalline grains), and there are L1-rich 2 Phase grains and poor L1 2 This multi-level soft and hard distribution structure leads to double back stress strengthening, producing a multi-level strengthening effect, while maintaining good plastic deformation ability, improving its strain hardening ability, improving fracture toughness, and improving the reliability and service life of the material.
[0029] 3. The homogenization heat treatment process eliminates the dendrites and segregation produced during the casting and hot forging process of the alloy, making the alloy structure more uniform and improving its mechanical strength.
[0030] 4. The multi-stage annealing process eliminates the internal stress and defects of the material, thereby improving its plasticity and ductility.
[0031] 5. The pre-aging process is conducive to the precipitation of small precipitates, which prevents excessive growth of grain size and also prevents excessive coarsening of the precipitates produced during annealing, which has an adverse effect on performance.
[0032] 6. The process parameters of each step in the preparation method are clear and easy to control, such as melting atmosphere, cold rolling deformation, annealing and aging temperature and time, etc. It has strong operability and is convenient for large-scale industrial production. It can stably prepare medium-entropy alloy materials with excellent performance, providing strong guarantee for its wide application in aerospace, automobile manufacturing, energy and other fields.
[0033] The present invention provides a high-strength, tough, crack-resistant nickel-based medium-entropy alloy and a preparation method thereof, and belongs to the technical field of medium-entropy alloys. The present invention optimizes and improves various aspects of the performance of medium-entropy alloys through carefully designed components and process. The initial cast alloy is obtained by accurately proportioning elements such as Ni, Co, Cr, Al, Ti, Mo, W, Fe, Zr, and smelting and casting, followed by hot forging, hot rolling, solid solution, cold rolling, multi-stage annealing and multi-stage aging treatment, to obtain a medium-entropy alloy with uneven grains and uneven precipitation phase structure, to achieve double back stress strengthening and precipitation phase strengthening, and to improve the strength of the alloy without reducing the plasticity of the alloy. Finally, under the process conditions of the present invention, a variety of microstructures with significant strengthening effects are generated inside the alloy, and a variety of strengthening mechanisms work synergistically, so that the alloy exhibits extremely high strength and good plasticity, and also exhibits high brittle fracture toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The engineering stress-strain curves of the samples obtained in Example 1 and Comparative Examples 1 and 2 after stretching;
[0035] Figure 2 EBSD image and grain size distribution diagram of the layered grain structure of the sample of Example 1 of the present invention;
[0036] Figure 3 FCC-L1 of the sample of Example 1 of the present invention 2 TEM images of the structures;
[0037] Figure 4 This is a TEM image of the structure of the sample after deformation in Example 1 of the present invention;
[0038] Figure 5 This is the JR curve diagram of the sample in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0040] Example 1
[0041] A high-strength, tough and crack-resistant nickel-based medium-entropy alloy comprises, in atomic percentage, 49% Ni, 22% Co, 15% Cr, 5% Al, 5% Ti, 1% Mo, 0.2% W, 0.5% Fe, 0.1% Zr, and the remainder is unavoidable impurities.
[0042] A high-strength, tough, crack-resistant nickel-based medium-entropy alloy has a layered structure with alternating distribution of residual deformation structure of nano-scale grains and recrystallization structure of micron-scale grains; the volume fraction of the residual deformation structure is 14%, and the grain size of the residual deformation structure is 67-130nm; the volume fraction of the recrystallization structure is 86%; and the grain size of the recrystallization structure is 0.64-1.84μm.
[0043] There are large-sized L1 precipitates in the partially recrystallized structure 2 Precipitation phase; Spherical ten-nanometer L1 is evenly distributed in the recrystallized structure 2 precipitated phase;
[0044] Large size L1 2 The size of the precipitated phase is 377-807nm, and the volume fraction is 30%;
[0045] Spherical ten nanometers L1 2 The size of the precipitated phase is 8.79-9.07 nm, and the volume fraction is 14%;
[0046] Hundreds of nanometer-scale L1 are embedded in the residual deformation structure 2 The size of the precipitated phase is 86-152 nm, and the volume fraction is 5%.
[0047] The microstructure of the high-strength, tough and crack-resistant nickel-based medium-entropy alloy is an incompletely recrystallized dual-phase structure, including a lamellar grain structure, a spherical 100-nanometer precipitate phase distributed in the residual deformation structure, and a spherical 10-nanometer L1 distributed in the recrystallized structure. 2 Precipitation phase and large size L1 precipitated only in part of the grains 2 Precipitation phase. Through the uneven hardness of the layered grains and the equally uneven hardness of the L1-rich 2 With poor L1 2 The microstructure of the grains can induce non-uniform deformation inside the grains, which requires the generation of geometrically necessary dislocations to coordinate the deformation, thereby successfully introducing double back stress strengthening and resulting in additional strengthening effects.
[0048] Traditional 3 Al type L1 2 The precipitate phase has the disadvantages of poor ductility, low thermal stability and high environmental brittleness, so it needs to be modified. Adding Co element to improve the ductility of the precipitate phase, Cr element to stabilize the precipitate phase structure, and Ti element to reduce environmental brittleness, finally forming (NiCoCr)3 (AlTi) element configuration L1 2 The precipitated phase, L1 of this configuration 2 The precipitated phase has a certain plastic deformation ability, and at the same time avoids stress concentration in the precipitated phase and premature fracture.
[0049] A method for preparing a high-strength, tough, and crack-resistant nickel-based medium-entropy alloy, in particular a method for preparing a high-volume fraction, multi-size nano-precipitation-reinforced high-strength, tough, and crack-resistant nickel-based medium-entropy alloy, comprising the following steps:
[0050] (1) The raw materials of the components are fully melted in an induction melting furnace under an argon atmosphere to obtain an ingot, the melting temperature is 1400° C., the melting time is 20 min, and the melting times are 5 times.
[0051] (2) The ingot in step (1) is subjected to hot forging, homogenization treatment, hot rolling, solution treatment, cold rolling, multi-stage annealing pre-aging, and aging treatment in sequence to obtain a high-strength, tough, crack-resistant nickel-based medium-entropy alloy (named CRAA).
[0052] The initial hot forging temperature is 1100°C, the final forging temperature is 900°C, the hot forging time is 15 minutes, and the deformation is 55%.
[0053] The temperature of the homogenization treatment was 1250°C and the holding time was 3 hours.
[0054] The hot rolling temperature is 1000°C, the total deformation is controlled at 50%, the hot rolled surface is the same as the hot forged surface, and finally a hot rolled plate with a thickness of about 15 mm is obtained, and a block alloy sample with a size of 5 mm×10 mm×40 mm is cut from the core of the plate.
[0055] The solution temperature is 1090°C, the solution time is 4h, and the cooling condition is air cooling.
[0056] The process parameters of the multi-pass cold rolling treatment must ensure that the sample thickness is reduced by about 80%. Specifically, a homogeneous block sample with an initial thickness of 5 mm is rolled and deformed at room temperature. The average pressure reduction before 2 mm is about 0.2 mm, and the average pressure reduction changes by about 0.1 mm when the rolling is about 1 mm. The final deformed rolled plate thickness is 20% of the initial thickness, and a rolled strip with a thickness of about 1 mm is finally obtained.
[0057] The multi-stage annealing temperatures are 900℃ and 950℃ respectively, and the annealing time is 8h. Each annealing treatment is 50℃ higher than the previous annealing treatment and the insulation time is the same; each annealing treatment requires air cooling to room temperature after leaving the furnace.
[0058] The pre-aging treatment temperature is 600°C, the pre-aging treatment time is 0.5h, and the cooling condition is air cooling.
[0059] The aging treatment temperature is 750°C, the aging treatment time is 2h, and the cooling condition is air cooling.
[0060] According to the requirements of GB / T228.1-2010 standard, the measured alloy mechanical properties are: tensile strength σ UTS is 1624MPa, and the yield strength σ y is 1259MPa, elongation at break ε T 23.7%, according to GB / T4161-2007 "Plane Strain Fracture Toughness K of Metallic Materials" ⅠC Experimental method》The fracture toughness obtained by the test is 80MPa·m 1 / 2 , the alloy has excellent strength-plasticity matching and crack resistance.
[0061] The high-strength, tough, and crack-resistant nickel-based medium-entropy alloy was analyzed using backscattered electron diffraction. Figure 2 The alloy has a layered structure, which is divided into residual deformation structure of nano-scale grains and recrystallization structure of micron-scale grains. The volume fraction of nano-crystals is 14%, and the grain size is 67-130nm; the volume fraction of ultra-fine crystals is 86%, and the grain size is 0.64-1.84μm.
[0062] The microstructure of the alloy was analyzed using transmission electron microscopy. Figure 3 As shown in the figure, some grains in the recrystallized structure have randomly shaped precipitates, with a size of 377-807nm and a volume fraction of 30%; some grains have no obvious large-sized precipitates; hundreds of nanometer-scale precipitates are embedded in the residual deformation structure, with a size of 86-152nm and a volume fraction of 5%; tens of nanometer-scale precipitates are precipitated in the recrystallized grains, with a size of 8.79-9.07nm and a volume fraction of 14%.
[0063] Comparative Example 1
[0064] A method for preparing a nickel-based medium-entropy alloy comprises the following steps:
[0065] (1) The raw materials of the components are fully melted in an induction melting furnace under an argon atmosphere to obtain an ingot, the melting temperature is 1400° C., the melting time is 20 min, and the melting times are 5 times.
[0066] (2) The ingot in step (1) is subjected to hot forging, homogenization treatment, hot rolling, solution treatment, cold rolling, and multi-stage annealing treatment in sequence to obtain a nickel-based medium entropy alloy (named CRA).
[0067] The initial hot forging temperature is 1100°C, the final forging temperature is 900°C, the hot forging time is 15 minutes, and the deformation is 55%.
[0068] The temperature of the homogenization treatment was 1250°C and the holding time was 3 hours.
[0069] The hot rolling temperature is 1000°C, the total deformation is controlled at 50%, the hot rolled surface is the same as the hot forged surface, and finally a hot rolled plate with a thickness of about 15 mm is obtained, and a block alloy sample with a size of 5 mm×10 mm×40 mm is cut from the core of the plate.
[0070] The solution temperature is 1090°C, the solution time is 4h, and the cooling condition is air cooling.
[0071] The process parameters of the multi-pass cold rolling treatment need to ensure that the sample thickness is reduced by about 80%, and finally a rolled strip with a thickness of about 1 mm is obtained.
[0072] The multi-stage annealing temperatures are 900°C and 950°C respectively, the annealing time is 8h, and the cooling conditions are air cooling.
[0073] Compared with Example 1, no pre-aging and aging treatments were performed.
[0074] According to the requirements of GB / T228.1-2010 standard, the measured alloy mechanical properties are: tensile strength σ UTS is 1420MPa, and the yield strength σ y is 1005MPa, elongation at break ε T 24.4%, according to GB / T4161-2007 "Plane Strain Fracture Toughness K of Metallic Materials" ⅠC Experimental method》The fracture toughness obtained by the test is 60MPa·m 1 / 2 , the alloy has high strength and good plasticity.
[0075] The high strength and fracture toughness nickel-based medium entropy alloy was analyzed using backscattered electron diffraction. Figure 2 The alloy has a layered structure of grains, which are divided into residual deformation structure of nano-scale grains and recrystallization structure of micron-scale grains. The volume fraction of nano-crystals is 20%, and the grain size is 59-125nm; the volume fraction of ultrafine crystals is 80%, and the grain size is 0.58-1.98μm.
[0076] The microstructure of the alloy was analyzed using transmission electron microscopy. Figure 3 As shown in the figure, some grains in the recrystallized structure have randomly shaped precipitates, with a size of 345-737nm and a volume fraction of 19%; some grains have no obvious large-sized precipitates; hundreds of nanometers of precipitates are embedded in the residual deformation structure, with a size of 67-121nm and a volume fraction of 6%; no tens of nanometers of precipitates are observed in the recrystallized grains.
[0077] Comparative Example 2
[0078] A method for preparing a coarse-grained medium-entropy alloy comprises the following steps:
[0079] (1) The raw materials of the components are fully melted in an induction melting furnace under an argon atmosphere to obtain an ingot, the melting temperature is 1400° C., the melting time is 20 min, and the melting times are 5 times.
[0080] (2) The ingot in step (1) is subjected to hot forging, homogenization treatment, hot rolling and solid solution treatment in sequence to obtain a coarse-grained medium-entropy alloy.
[0081] The initial hot forging temperature is 1100°C, the final forging temperature is 900°C, the hot forging time is 15 minutes, and the deformation is 55%.
[0082] The temperature of the homogenization treatment was 1250°C and the holding time was 3 hours.
[0083] The hot rolling temperature is 1000°C, the total deformation is controlled at 50%, the hot rolled surface is the same as the hot forged surface, and finally a hot rolled plate with a thickness of about 15 mm is obtained, and a block alloy sample with a size of 5 mm×10 mm×40 mm is cut from the core of the plate.
[0084] The solution temperature is 1090°C, the solution time is 4h, and the cooling condition is air cooling.
[0085] Compared with Example 1, cold rolling, multi-stage annealing, pre-aging and aging treatment are not performed.
[0086] According to the requirements of GB / T228.1-2010 standard, the measured alloy mechanical properties are: tensile strength σ UTS is 1099MPa, and the yield strength σ y is 767MPa, elongation at break ε T 25.2%, according to GB / T4161-2007 "Plane Strain Fracture Toughness K of Metallic Materials" ⅠC Experimental method》The fracture toughness obtained by the test is 55MPa·m 1 / 2 The alloy strength is lower and the work hardening ability is not as good as the alloys in Example 1 and Example 2, but the alloy has good plasticity.
[0087] The microstructure and composition of the coarse-grained mesoentropy alloy were obtained by transmission electron microscopy. The alloy has a uniform structure with only coarse equiaxed grains and a grain size of 100 to 200 μm. The grains are uniformly distributed with spherical L1 2 Phase, spherical L1 2 The phase diameter is 100-150 nm, and the phase volume fraction is 43.18%.
[0088] The present invention also provides a performance test and characterization method involved in the above case, including the following contents:
[0089] Mechanical properties test method: The samples prepared in the examples and comparative examples were subjected to electric spark wire cutting to obtain standard room temperature tensile specimens with a shape similar to "dog bones". During the wire cutting process, the direction of room temperature tensile should be consistent with the rolling direction of the rollers during cold rolling. The plane size of the room temperature tensile specimen is 4×29mm 2 , thickness 1mm, gauge section cross section 2×1mm 2 For quasi-static stretching, the basic mechanical properties of the samples were tested by uniaxial stretching using an Instron 5982 room temperature stretching machine, and the stretching rate was 3×10 -4 s -1 , and get Figure 1 Engineering stress-strain curve shown.
[0090] Fracture toughness test method: According to GB / T 4161-2007 "Plane strain fracture toughness K of metal materials ⅠC Experimental method》Testing fracture toughness.
[0091] Microstructure characterization method: The samples prepared and mechanically tested in the examples and comparative examples were subjected to wire-cut electrospark cutting to obtain 1×1 mm 2 , 9mm long electron microscope specimen. For EBSD analysis, the specimen was polished on sandpaper, and the sandpaper used was 400#, 800#, 1200#, and 2000#; the polished specimen was polished with a polishing machine, and 2.5w diamond paste was used for polishing, and the polishing time was 8 to 15min; the polished specimen was electropolished, and the electrolyte was composed of perchloric acid: anhydrous ethanol in a ratio of 1:9, the ambient temperature was 25°C, the voltage value was 12V, and the electrolysis time was 2s. The electrolyzed specimen was observed for its structure using the EBSD system under a FIB / SEM dual-beam system (Zeiss Auriga) electron microscope, and the following was obtained: Figure 2 The structure shown. For TEM analysis, the sample was sanded to 40μm with sandpaper of 400#, 800#, 1200#, and 2000#; the sample was punched into a 3mm thin slice using a punching machine; the thin slice sample was double-sprayed, and the double-spraying liquid was made of perchloric acid: anhydrous ethanol in a ratio of 1:9, the ambient temperature was -30°C, the voltage value was 20V, and the double-spraying time was 3min. The structure of the sample after electrolysis was observed under a FEI Tecnai 20 high-resolution transmission microscope (lanthanum hexaboride), and the following was obtained: Figure 3 , 4 The organization shown.
[0092] Table 1 below shows Figure 1 In addition, the yield strength, tensile strength and elongation at break of representative samples under each heat treatment condition were statistically analyzed.
[0093] Table 1 Yield strength, tensile strength and elongation at break data table
[0094]
[0095] In Table 1, 950°C for 16h means that the multi-stage annealing temperatures are 900°C and 950°C, and the annealing time is 8h.
[0096] The present invention provides a method for inducing a double heterogeneous interface with L1 2 The solution of preparing high-strength, tough and crack-resistant nickel-based alloy by combining precipitation-strengthened structure greatly improves the performance of the entropy alloy in this composition. For CRA and CRAA, their ductility at room temperature is almost the same as that of Comparative Examples 1 and 2, but their yield strength increases by 238MPa and 492MPa respectively, and their tensile strength increases by 321MPa and 525MPa respectively. This is due to the introduction of multiple strengthening mechanisms into the alloy structure after hot forging-hot rolling-solid solution-cold rolling, such as Figure 4 As shown in Figure 2, the alloy exhibits a rich substructure during deformation, including dislocation cells, a large number of stacking fault networks, nano-deformation twins, and high-density LC locks (e.g. Figure 4 (a)), these substructures can reduce the free path of dislocation movement and produce dynamic Hall-Petch effect (such as Figure 4 (b) shows), which enhances the work hardening ability of the alloy. In the alloy prepared by the present invention, the presence of uneven distribution L1 2 Phase, alternating distribution of lamellar grains, nanoscale fine grains, so that the stress can be more evenly distributed in the ultrafine grains and γ phase, effectively reducing the influence of stress concentration and delaying the occurrence of cracks. Figure 5 The curve (red line is the fitting curve) of the experimentally obtained J integral value and the corresponding crack extension length Δa is drawn. The starting point of the JR curve is selected, and a specific crack growth length of 0.2 mm is offset on the horizontal axis according to the standard (such as ASTM E1820), and an offset straight line parallel to the starting section of the curve is drawn. The intersection corresponds to the J of the material. ⅠC The test results are shown in Table 2 below.
[0097] Table 2 J-R curve data table
[0098]
[0099] In the above table, P max / P Q is the ratio of the maximum load to the yield load in the fracture test; 10J Q / σ Y is the ratio of ten times the J-integral critical value to the yield strength; J ⅠC is the critical J integral; K ⅠCis the critical stress intensity factor.
[0100] The high-strength, tough, and crack-resistant nickel-based medium-entropy alloy mentioned in the present invention contains multi-sized, high-density L1 2 Precipitation phase. Adding excessive nickel elements during composition design can stabilize the face-centered cubic phase of the face-centered cubic matrix, provide a good plastic foundation for the alloy, and enhance the corrosion resistance of the alloy. In addition, during the precipitation process of the precipitated phase, the elements inside the alloy are redistributed, and the nickel elements with high stacking fault energy are enriched inside the precipitated phase, thereby reducing the stacking fault energy of the matrix, and the higher rheological stress stimulates a variety of deformation mechanisms, greatly improving the strain hardening ability of the alloy. Containing L1 2 The interface between the grains of the phase and the grains of the γ matrix alone will produce a strain gradient. This strain gradient promotes the generation and movement of dislocations, thereby enhancing the strength and hardness of the material. It is worth mentioning that the back stress effect improves the strain hardening ability of the material and further improves its mechanical properties. Nanoscale small grains and (with or without L1 2 The strength difference of micron-scale grains may lead to double back stress strengthening: 2 In the ultrafine grain system of nanocrystalline phase and γ matrix, if there are also nanoscale small grains, the mechanical incompatibility between grains of different sizes and phases will lead to more complex stress distribution and dislocation behavior. The interface between nanocrystalline and ultrafine grains will produce additional dislocation accumulation, which will further enhance the back stress strengthening effect. At the same time, it also allows the stress to be more evenly distributed in the ultrafine grains and γ phase, effectively reducing the influence of stress concentration and delaying the occurrence of cracks. Based on the model of dislocation cutting precipitation phase, it can be calculated that under the cutting mechanism, high-density L1 2 The strength contributed by the precipitated phase is 665MPa, accounting for 41% of the tensile strength. This double back stress strengthening effect will not only increase the strength of the material, but also improve its strain hardening ability and crack growth resistance. It can be seen that the combination of the high strength of nano-grains and the ductility of ultrafine grains helps to optimize the material properties.
[0101] Example 2
[0102] A high-strength, tough and crack-resistant nickel-based medium-entropy alloy comprises, in atomic percentage, 48% Ni, 23% Co, 16% Cr, 4% Al, 6% Ti, 2% Mo, 0.1% W, 0.7% Fe, 0.01% Zr, and the remainder is unavoidable impurities.
[0103] A high-strength, tough, crack-resistant nickel-based medium-entropy alloy has a layered structure with alternating distribution of residual deformation structure of nano-scale grains and recrystallization structure of micron-scale grains; the volume fraction of the residual deformation structure is 12%, and the grain size of the residual deformation structure is 67-130nm; the volume fraction of the recrystallization structure is 88%; and the grain size of the recrystallization structure is 0.64-1.84μm.
[0104] There are large-sized L1 precipitates in the partially recrystallized structure 2 Precipitation phase; Spherical ten-nanometer L1 is evenly distributed in the recrystallized structure 2 precipitated phase;
[0105] Large size L1 2 The size of the precipitated phase is 377-807nm, and the volume fraction is 29%;
[0106] Spherical ten nanometers L1 2 The size of the precipitated phase is 8.79-9.07 nm, and the volume fraction is 13%;
[0107] Hundreds of nanometer-scale L1 are embedded in the residual deformation structure 2 The size of the precipitated phase is 86-152 nm, and the volume fraction is 4%.
[0108] The microstructure of the high-strength, tough and crack-resistant nickel-based medium-entropy alloy is an incompletely recrystallized dual-phase structure, including a lamellar grain structure, a spherical 100-nanometer precipitate phase distributed in the residual deformation structure, and a spherical 10-nanometer L1 distributed in the recrystallized structure. 2 Precipitation phase and large size L1 precipitated only in part of the grains 2 Precipitation phase. Through the uneven hardness of the layered grains and the equally uneven hardness of the L1-rich 2 With poor L1 2 The microstructure of the grains can induce non-uniform deformation inside the grains, which requires the generation of geometrically necessary dislocations to coordinate the deformation, thereby successfully introducing double back stress strengthening and resulting in additional strengthening effects.
[0109] A method for preparing a high-strength, tough, and crack-resistant nickel-based medium-entropy alloy, in particular a method for preparing a high-volume fraction, multi-size nano-precipitation-reinforced high-strength, tough, and crack-resistant nickel-based medium-entropy alloy, comprising the following steps:
[0110] (1) The raw materials of the components are fully melted in an induction melting furnace under an argon atmosphere to obtain an ingot, the melting temperature is 1350° C., the melting time is 15 min, and the melting number is 6 times.
[0111] (2) The ingot in step (1) is subjected to hot forging, homogenization treatment, hot rolling, solution treatment, cold rolling, multi-stage annealing pre-aging, and aging treatment in sequence to obtain a high-strength, tough, crack-resistant nickel-based medium-entropy alloy (named CRAA).
[0112] The initial hot forging temperature is 1050°C, the final forging temperature is 950°C, the hot forging time is 10 min, and the deformation is 50%.
[0113] The temperature of the homogenization treatment was 1200°C and the holding time was 3.5 hours.
[0114] The hot rolling temperature was 950° C., the total deformation was controlled at 40%, and block alloy samples with a size of 5 mm×10 mm×40 mm were cut from the core of the plate.
[0115] The solution temperature is 1120°C, the solution time is 6h, and the cooling condition is air cooling.
[0116] The process parameters of the multi-pass cold rolling treatment must ensure that the sample thickness is reduced by about 80%. Specifically, a homogeneous block sample with an initial thickness of 5 mm is rolled and deformed at room temperature. The average pressure reduction before 2 mm is about 0.2 mm, and the average pressure reduction changes by about 0.1 mm when the rolling is about 1 mm. The final deformed rolled plate thickness is 20% of the initial thickness, and a rolled strip with a thickness of about 1 mm is finally obtained.
[0117] The multi-stage annealing temperatures are 950℃ and 1000℃ respectively, and the annealing time is 2h. Each annealing treatment is 50℃ higher than the previous annealing treatment and the insulation time is the same; each annealing treatment requires air cooling to room temperature after leaving the furnace.
[0118] The pre-aging treatment temperature is 650°C, the pre-aging treatment time is 1h, and the cooling condition is air cooling.
[0119] The aging treatment temperature is 700°C, the aging treatment time is 1h, and the cooling condition is air cooling.
[0120] According to the requirements of GB / T228.1-2010 standard, the measured alloy mechanical properties are: tensile strength σ UTS is 1608MPa, and the yield strength σ y is 1298MPa, elongation at break ε T 23.9%, according to GB / T4161-2007 "Plane Strain Fracture Toughness K of Metallic Materials" ⅠC Experimental method》The fracture toughness obtained by the test is 70MPa·m 1 / 2 , the alloy has excellent strength-plasticity matching and crack resistance.
[0121] A high-strength, tough, crack-resistant nickel-based medium-entropy alloy with applications in aerospace, automobile manufacturing, and energy fields.
[0122] Example 3
[0123] A high-strength, tough and crack-resistant nickel-based medium-entropy alloy comprises, in atomic percentage, 50% Ni, 21% Co, 14% Cr, 6% Al, 4% Ti, 0.5% Mo, 0.5% W, 0.1% Fe, 0.05% Zr, and the remainder is unavoidable impurities.
[0124] A high-strength, tough, crack-resistant nickel-based medium-entropy alloy has a layered structure with alternating distribution of residual deformation structure of nano-scale grains and recrystallization structure of micron-scale grains; the volume fraction of the residual deformation structure is 15%, and the grain size of the residual deformation structure is 67-130nm; the volume fraction of the recrystallization structure is 85%; and the grain size of the recrystallization structure is 0.64-1.84μm.
[0125] There are large-sized L1 precipitates in the partially recrystallized structure 2 Precipitation phase; Spherical ten-nanometer L1 is evenly distributed in the recrystallized structure 2 precipitated phase;
[0126] Large size L1 2 The size of the precipitated phase is 377-807 nm, and the volume fraction is 31%;
[0127] Spherical ten nanometers L1 2 The size of the precipitated phase is 8.79-9.07 nm, and the volume fraction is 15%;
[0128] Hundreds of nanometer-scale L1 are embedded in the residual deformation structure 2 The size of the precipitated phase is 86-152 nm, and the volume fraction is 6%.
[0129] The microstructure of the high-strength, tough and crack-resistant nickel-based medium-entropy alloy is an incompletely recrystallized dual-phase structure, including a lamellar grain structure, a spherical 100-nanometer precipitate phase distributed in the residual deformation structure, and a spherical 10-nanometer L1 distributed in the recrystallized structure. 2 Precipitation phase and large size L1 precipitated only in part of the grains 2 Precipitation phase. Through the uneven hardness of the layered grains and the equally uneven hardness of the L1-rich 2 With poor L1 2 The microstructure of the grains can induce non-uniform deformation inside the grains, which requires the generation of geometrically necessary dislocations to coordinate the deformation, thereby successfully introducing double back stress strengthening and resulting in additional strengthening effects.
[0130] A method for preparing a high-strength, tough, and crack-resistant nickel-based medium-entropy alloy, in particular a method for preparing a high-volume fraction, multi-size nano-precipitation-reinforced high-strength, tough, and crack-resistant nickel-based medium-entropy alloy, comprising the following steps:
[0131] (1) The raw materials of the components are fully melted in an induction melting furnace under an argon atmosphere to obtain an ingot, the melting temperature is 1450° C., the melting time is 18 min, and the melting times are 5 times.
[0132] (2) The ingot in step (1) is subjected to hot forging, homogenization treatment, hot rolling, solution treatment, cold rolling, multi-stage annealing pre-aging, and aging treatment in sequence to obtain a high-strength, tough, crack-resistant nickel-based medium-entropy alloy (named CRAA).
[0133] The initial hot forging temperature is 1150°C, the final forging temperature is 900°C, the hot forging time is 12 minutes, and the deformation is 60%.
[0134] The temperature of the homogenization treatment was 1290°C and the holding time was 3 hours.
[0135] The hot rolling temperature was 980°C, the total deformation was controlled at 45%, and block alloy samples with a size of 5 mm×10 mm×40 mm were cut from the core of the plate.
[0136] The solution temperature is 1090°C, the solution time is 5h, and the cooling condition is air cooling.
[0137] The process parameters of the multi-pass cold rolling treatment must ensure that the sample thickness is reduced by about 80%. Specifically, a homogeneous block sample with an initial thickness of 5 mm is rolled and deformed at room temperature. The average pressure reduction before 2 mm is about 0.2 mm, and the average pressure reduction changes by about 0.1 mm when the rolling is about 1 mm. The final deformed rolled plate thickness is 20% of the initial thickness, and a rolled strip with a thickness of about 1 mm is finally obtained.
[0138] The multi-stage annealing temperatures are 950℃ and 980℃ respectively, and the annealing time is 24h. Each annealing treatment is 30℃ higher than the previous annealing treatment and the insulation time is the same; each annealing treatment requires air cooling to room temperature after leaving the furnace.
[0139] The pre-aging treatment temperature is 620°C, the pre-aging treatment time is 1h, and the cooling condition is air cooling.
[0140] The aging treatment temperature is 800°C, the aging treatment time is 8h, and the cooling condition is air cooling.
[0141] According to the requirements of GB / T228.1-2010 standard, the measured alloy mechanical properties are: tensile strength σ UTS is 1725MPa, and the yield strength σ y is 1269MPa, elongation at break ε T 22.1%, according to GB / T4161-2007 "Plane Strain Fracture Toughness K of Metallic Materials" ⅠC Experimental method》The fracture toughness obtained by the test is 100MPa·m1 / 2 , the alloy has excellent strength-plasticity matching and crack resistance.
[0142] A high-strength, tough, and crack-resistant nickel-based medium-entropy alloy for use in aerospace, automobile manufacturing, and energy fields. It should be understood that in order to simplify the present disclosure and help understand one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, the various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, the disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those explicitly stated in each claim. More specifically, as reflected in the claims, the inventive aspects lie in less than all the features of the previously disclosed embodiments. Therefore, the claims that follow the specific embodiment are hereby expressly incorporated into the specific embodiment, with each claim itself serving as a separate embodiment of the present invention.
[0143] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0144] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength, tough, crack-resistant nickel-based medium-entropy alloy, characterized in that: In terms of atomic percentage, the composition of the medium entropy alloy includes: Ni 48-50%, Co 21-23%, Cr 14-16%, Al 4-6%, Ti 4-6%, Mo 0.5-2%, W 0.1-0.5%, Fe 0.1-0.7%, Zr 0.01-0.1%, and the remainder is inevitable impurities.
2. A high-strength, tough, crack-resistant nickel-based medium-entropy alloy according to claim 1, characterized in that: A layered structure with alternating distribution of residual deformation structure of nano-scale grains and recrystallized structure of micron-scale grains; the volume fraction of the residual deformation structure is 12-15%, and the volume fraction of the recrystallized structure is 85-88%; Large-sized L12 precipitates are precipitated in some recrystallized structures; spherical L12 precipitates of ten nanometers are evenly distributed in the recrystallized structures; The size of the large-sized L12 precipitate phase is 377-807 nm, and the volume fraction is 29-31%; The size of the spherical ten-nanometer L12 precipitate phase is 8.79-9.07 nm, and the volume fraction is 13-15%; The residual deformation structure is embedded with hundreds of nanometer-scale L12 precipitates, whose size is 86 to 152 nm and volume fraction is 4 to 6%.
3. A high-strength, tough, crack-resistant nickel-based medium-entropy alloy according to claim 2, characterized in that: The grain size of the residual deformation structure is 67 to 130 nm.
4. A high-strength, tough, crack-resistant nickel-based medium-entropy alloy according to claim 2, characterized in that: The grain size of the recrystallized structure is 0.64 to 1.84 μm.
5. A high-strength, tough, crack-resistant nickel-based medium-entropy alloy according to claim 1, characterized in that: The yield strength at room temperature is 1259-1298 MPa, the tensile strength is 1608-1725 MPa, the elongation at break is 22.1-23.9%, and the fracture toughness is 70-100 MPa·m 1 / 2 .
6. A method for preparing a high-strength, tough, crack-resistant nickel-based medium-entropy alloy according to any one of claims 1 to 5, characterized in that: The following steps are involved: S01, fully melting the raw materials of the components in an induction melting furnace under an argon atmosphere to obtain an ingot, the melting temperature is 1350-1450° C., the melting time is 15-20 min, and the melting number is at least 5 times; S02, sequentially performing hot forging, homogenization treatment, hot rolling, solution treatment, cold rolling, multi-stage annealing, pre-aging, and aging treatment on the ingot in S01 to obtain a high-strength, tough, and crack-resistant nickel-based medium-entropy alloy; The hot forging temperature is 1050-1150°C, the final forging temperature is 900-950°C, the hot forging time is 10-15 minutes, and the deformation is controlled at 50-60%; The homogenization treatment is to keep the temperature at 1200-1290℃ for at least 3 hours, and then air cool it; The hot rolling temperature is 950-1000°C, and the total deformation is controlled at 40-50%; Solution treatment is carried out at 1090-1120℃ for 4-6 hours, followed by air cooling. The process parameters of the multi-pass cold rolling treatment must ensure that the sample thickness is reduced by 80%; The multi-stage annealing temperature is 900-1000℃, and the annealing time is 2-24h; each annealing treatment is 30-50℃ higher than the previous annealing treatment, and the heat preservation time is the same; each annealing treatment must be air-cooled to room temperature after leaving the furnace; The pre-aging treatment temperature is 600-650°C, the treatment time is 0.5-1h, and the cooling method is air cooling; The aging treatment temperature is 700-800°C, the aging treatment time is 1-8h, and the cooling method is air cooling.
7. The preparation method according to claim 6, characterized in that: During hot rolling, the hot rolled surface is the same as the hot forged surface, and finally a hot rolled plate with a thickness of 15 mm is obtained, and a block alloy sample with a size of 5 mm×10 mm×40 mm is cut from the core of the plate.
8. The preparation method according to claim 7, characterized in that: The multi-pass cold rolling process is as follows: a homogeneous block sample with an initial thickness of 5 mm is rolled and deformed at room temperature, the average pressure reduction before 2 mm is 0.2 mm, and the average pressure reduction changes to 0.1 mm when rolling 1 mm. The final deformed rolled plate thickness is 20% of the initial thickness, i.e. 1 mm.
9. The preparation method according to claim 6, characterized in that: Multi-stage annealing is a two-stage annealing process.
10. Application of a high-strength, toughness and crack-resistant nickel-based medium-entropy alloy according to any one of claims 1 to 5 in the fields of aerospace, automobile manufacturing and energy.
Citation Information
Cited By
High-toughness and high-entropy alloy with dynamically-enhanced dislocation cells and preparation method of high-toughness and high-entropy alloy
CN120479940A
Variable-temperature aging strengthening low-cost Fe-based medium-entropy alloy and preparation method thereof
CN121161180A